Implementation of Aswaja An-Nahdliyah Value-Based Religious Moderation Education for Students - Mufaizin Mufaizin; Junaidi Junaidi; Moh. Holil Baitaputra (Journal of Innovative and Creativity, 2025)
This study aims to analyse the implementation of religious moderation education based on Aswaja An-Nahdliyah values in STAI Darul Hikmah Bangkalan students. Religious moderation education is very important in shaping an attitude of tolerance, inclusiveness, and respect for differences in a plural society. The research method used is qualitative with a case study approach. Data were collected through participatory observation, in-depth interviews, and documentation studies. The results showed that the values of tawassuth (moderate), tasamuh (tolerance), tawazun (balance), and i'tidal (justice) were internalised through the curriculum, religious activities, and the example of lecturers and campus leaders. These values are applied in Aswaja courses, Islamic studies, Friday sermons, and student organisation activities. Co-curricular activities such as interfaith seminars, open discussions, and dialogue between Islamic organisations strengthen the internalisation of moderation values. Students also practice these values through community service. This moderation education programme is effective in shaping the character of students who are moderate, peace-loving, and passionate about nationalism. The inclusive campus environment is a supporting factor for the success of this programme. The research recommends strengthening Aswaja-based education and periodic evaluation to remain relevant to the challenges of the times..